التحديات التي تواجه المصارف التجارية في منح التمويل الأخضر دراسة تطبيقية على مصرف الصحارى (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of challenges (legislative and regulatory, technical and human resources, financial, and market challenges) facing Sahara Bank in providing green financing. To achieve the study's objectives, a descriptive-analytical approach was adopted as the most suitable methodology. The study sample consisted of a purposive sample of 45 employees, including department managers and heads of relevant sections within Sahara Bank's general management. A questionnaire was designed and distributed to the target sample, yielding 40 responses that matched the study's questions. The study employed appropriate statistical methods, including measures of central tendency, weighted arithmetic mean, and standard deviation. A one-sample t-test was also used to test the study's hypotheses. The results indicated a high level of challenges hindering the bank's provision of green financing. Therefore, the study recommends that Sahara Bank adopt a comprehensive corporate strategy for green financing, integrated within its overall strategy, to ensure a balance between financial objectives and environmental sustainability. In strengthening its role in supporting sustainable development.
Keywords: Green finance – Sustainable development – Sahara Bank